(untitled) (Journal of Applied and Natural Science, 2015)
Plant growth promoting rhizobacteria are the soil bacteria inhabiting around/on the root surface and are directly or indirectly involved in promoting plant growth and development via production and secretion of various regulatory chemicals in the vicinity of rhizosphere. There has been much research interest in PGPB and there is now an increasing number of PGPB being commercialized for various crops. Today a lot of efforts have been made for searching and investigating the PGPB and their mode of action, so that they can be exploited commercially as biofertilizers. Because of the various challenges faced in screening, formulation, and application, PGPB have yet to fulfill their promise and potential as commercial inoculants. Recent progress in our understanding of their diversity, colonization ability, mechanisms of action, formulation, and application should facilitate their development as reliable components in the management of sustainable agricultural systems. Several reviews have discussed specific aspects of PGPB as bioinoculants. We have tried to critically evaluate the current status of bacterial inoculants for contemporary agriculture in developed and developing countries. This review focuses on some important information regarding the biofertilizing potential of some important group of microbes, their formulations, their application for the development of sustainable technology, scope of improvement by genetic engineering, steps to be undertaken for their commercialization and their future prospects.